Peran Jigsaw Dan Problem Solving Dalam Meningkatkan Berfikir Solutif Siswa Di SD Muhammad Al-Unaizy - Irwan Desiharto; Dede Maulana Malik; Siti Qomariyah (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
One of the teacher competencies that must be mastered is managing the class with various learning models, it aims to create a productive and two-way classroom atmosphere. Managing an elementary school class is a challenge in itself for the teacher because he must be able to control students to stay focused and get the desired results. Among the learning models in the classroom are the jigsaw model and problem solving. The application of the jigsaw model and problem solving was carried out at SD Muhammad Al-Unaizy by taking two samples, namely class V and class VI. The research method applied is descriptive qualitative analysis by engaging directly in learning with data collection techniques namely: Observation, Documentation, and interviews. The results of the research that we obtained at the location showed that the jigsaw mode and problem solving patterns had been applied by PAI and Tajwid teachers, and the result was the creation of active, productive, two-way learning, and students were encouraged to learn independently and think solutively and express their abilities. in front of the class.